2009
DOI: 10.1016/s1734-1140(09)70008-8
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of the flavonoid quercetin

Abstract: The blood pressure lowering effect of a fruit and vegetable-rich diet is a necessary dietary lifestyle measure now included the guidelines for the management of arterial hypertension. Furthermore, flavonoids represent a major class of plant polyphenolics. The present review addresses the antihypertensive effect of quercetin, one of the most abundant flavonoids present in fruits and vegetables, and probably the best studied flavonoid because of its high biological activity. Quercetin has been shown to induce a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(196 citation statements)
references
References 43 publications
4
179
0
6
Order By: Relevance
“…The presence of high levels of biologically active polyphenolic compounds, such as the flavonoids, is a likely health-promoting factor. Flavonoids have repeatedly been shown to improve cardiovascular diseases including hypertension, ischemic heart disease, and stroke (Hertog et al, 1993;Keli et al, 1996;Perez-Vizcaino et al, 2009). It has been further shown that flavonoids protect and improve endothelial function (Engler et al, 2004;Vita, 2005;Hodgson, 2006;Grassi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of high levels of biologically active polyphenolic compounds, such as the flavonoids, is a likely health-promoting factor. Flavonoids have repeatedly been shown to improve cardiovascular diseases including hypertension, ischemic heart disease, and stroke (Hertog et al, 1993;Keli et al, 1996;Perez-Vizcaino et al, 2009). It has been further shown that flavonoids protect and improve endothelial function (Engler et al, 2004;Vita, 2005;Hodgson, 2006;Grassi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies, together with data from animal models and some clinical trials, suggest a role of dietary flavonoids in the prevention of CVD and other age-related chronic diseases (108)(109)(110) . The flavonol quercetin exhibits a wide range of physiological effects such as inhibition of LDL-oxidation, lowering of arterial blood pressure and platelet aggregation, and improvement of endothelial function as shown in animal models and in human subjects (111)(112)(113)(114)(115)(116)(117) . Furthermore, cell culture and animal studies indicate a potent anti-inflammatory activity of quercetin (116,(118)(119)(120) .…”
Section: Flavonoidsmentioning
confidence: 99%
“…More recently, beneficial effects on blood pressure and heart disease have been described (Perez-Vizcaino et al 2009;Han et al 2009;Jung et al 2013). With regard to obesity, very little work has been carried out to date.…”
Section: Introductionmentioning
confidence: 99%